RETROSPECTIVE ANALYSIS OF THE PROCESS OF VIETNAM’S INTERNATIONAL ECONOMIC INTEGRATION - Nguen, Thi Thu Lin (Journal of European Economy, 2018)
The article is devoted to thorough examination and evaluation of the process of Vietnam's international economic integration from the XIXth century until the present time. Based on Vietnam's experience, the author elaborates conditions necessary for effective integration of the national economy into the world economy.